Obstructive sleep apnea and neurocognitive function in a Hispanic/Latino population - Ramos, Alberto R. (Neurology, 2015)
OBJECTIVE: We evaluated the association between obstructive sleep apnea (OSA) and neurocognitive function among community-dwelling Hispanic/Latino individuals in the United States. METHODS: Cross-sectional analysis of the Hispanic Community Health Study/Study of Latinos middle-aged and older adults, aged 45 to 74 years, with neurocognitive test scores at baseline measurements from 2008 to 2011. Neurocognitive scores were measured using the Word Fluency (WF) Test, the Brief–Spanish English Verbal Learning Test (SEVLT), and the Digit Symbol Substitution (DSS) Test. OSA was defined by the apnea-hypopnea index (AHI). Multivariable linear regression models were fit to evaluate relations between OSA and neurocognitive scores. RESULTS: The analysis consisted of 8,059 participants, mean age of 56 years, 55% women, and 41% with less than high school education. The mean AHI was 9.0 (range 0–142; normal AHI <5/h). There was an association between the AHI and all 4 neurocognitive test scores: Brief-SEVLT–sum (β = −0.022) and –recall (β = −0.010), WF (β = −0.023), and DSS (β = −0.050) at p < 0.01 that was fully attenuated by age. In the fully adjusted regression model, female sex was a moderating factor between the AHI and WF (β = −0.027, p < 0.10), SVELT-sum (β = −0.37), SVELT-recall (β = −0.010), and DSS (β = −0.061) at p < 0.01. CONCLUSION: OSA was associated with worse neurocognitive function in a representative sample of Hispanic/Latino women in the United States.